Treatment of neglected elbow dislocations with combination of speed V-Y muscleplasty and intra-articular injection of hydrocorticosone - Bansal, P; Lal, H; Khare, R; Mittal, D (Kathmandu University Medical Journal, 2010)
Neglected dislocations of the elbow are not uncommon in developing countries. We report case series of 3 cases of neglected dislocations of elbow. All the three cases were treated by combination of Speeds procedure and intraarticular injection of 25mg of hydrocorticosone acetate in 5ml of distilled water. Mean time from injury was 5 months and mean follow-up was 10 months. According to Mayo Elbow Performance Index, 2 outcomes were excellent and 1 outcome was good. Key words: Dislocations; elbow; neglected. DOI: 10.3126/kumj.v8i1.3229 Kathmandu University Medical Journal (2010), Vol. 8, No. 1, Issue 29, 91-94